Ecoturismo e Mudança Social na Amazônia Rural: efeitos sobre o papel da mulher e as relações de gênero - Nelissa Peralta (Universidade Federal do Paraná, 2008)
Ecotourism has been developed to improve the living standards of local people, especially in rural areas, but there are few researches analyzing what such projects represent to individuals within households. This article discusses social change in the domestic sphere, especially in reference to the role of women and gender relations. The research was carried out in a protected area (Sustainable Development Reserve) in the Middle Solimões River region. The methods employed were participant observation and open-ended interviews. The research demonstrated that ecotourism generated significant income, raising domestic income in 148% in one of the villages studied. Access to income and wage employment gave more economic independence to women, more power in allocating domestic resources, and better access to communication networks outside the domestic sphere. It also promoted discussions about the inequalities in gender relations, but it failed to incite a decrease of such inequalities.